Penanaman Kesadaran Tentang Pentingnya Kesehatan Mental Kepada Remaja - Eva Siti Faridah; Munakhiroh El Hajar; Zaeni Dahlan; Ahmad Ridwan; Siskha Putri Sayekti; Ernawati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
According to the Indonesia-National Adolescent Mental Health Survey 2022, 15.5 million (34.9 percent) teenagers experience mental problems and 2.45 million (5.5 percent) teenagers experience mental disorders. Youth mental health is considered a concern and the current situation may cause concern and require government action. Mental health has become a concern for the government, but has not yet become a priority. Awareness of the importance of mental health is still very low in Indonesia. Responding to the situation above, it is appropriate for the Indonesian people to educate each other and increase awareness about mental health. So it is necessary to instill awareness about mental health among teenagers. The methods used in community service consist of the preparatory stage of conducting a survey of the perceived mental health of junior high school students and interviews, the implementation stage by providing material for raising awareness about mental health to Muhammadiyah 2 Middle School students, the report and evaluation stage. The results of the mental health survey of students at SMP Muhammadiyah 2 showed symptoms. 12% of students answered always, 16% of students answered often, and 40% of students answered sometimes. Students answered never 62%. This means that the majority of junior high school students experience mental health problems at any time and according to the Likert scale table are included in the moderate category. Judging from the symptoms, this problem can still be overcome. The provision of material about mental health to Muhammadiyah 2 Middle School students was received with enthusiasm and enthusiasm, followed by discussion and questions and answers. Efforts to increase awareness about adolescent mental health by providing education involving all stakeholders: adolescents, parents, families, school principals, teachers and the community. It is hoped that this activity can increase youth productivity, avoid various diseases, improve communication skills and make life more successful.